RWC Update: DRCR Retina Network Protocol AC, Step Therapy, and Clinical Practice Implications; Central Retinal Vein Occlusion with Secondary Branch Retinal Artery Occlusion and Incidental Myelinated Nerve Fiber Layer and CHRPE - Sharma, Ashish; Wu, Lihteh; Bloom, Steven; Stanga, Paulo; Rachitskaya, Aleksandra V.; Gibson, Will; Rezaei, Kourous A. (Ophthalmic surgery, lasers & imaging, 2023)
Of note, individuals with significant renal disease, defined as a history of chronic renal failure requiring dialysis or kidney transplant; patients with BCVA worse than 20/320; and patients with uncontrolled hypertension, recent major intraocular surgery, recent initiation of intensified insulin therapy, recent panretinal photocoagulation, and/or recent anti-vascular endothelial growth factor treatment were not eligible to participate in the study. When applying the results of the study, the concern is the treatment approaches may not reflect those most commonly used in clinical practice (eg, treat and extend approach, lack of six months loading dosing, and lack of monthly visits in the first year). [...]the automated algorithm used in the study would not be available to retina specialists in real-world situations. [...]it is important to keep in mind that over the 2-year period of Protocol AC, approximately 70% of the patients in the bevacizumab-first group had their treatment switched to aflibercept. [...]57% of these patients had treatment switched between 12 weeks and 24 weeks (ie, only after the three treatments). The counter argument is that step therapy can result in restricted opportunity for the physician to act on clinical judgment for each particular patient, excessive administrative burdens, and potential delays in care.5 It has been suggested that Protocol AC provides the a needed evidence for step therapy efficacy and safety and that the step therapy approach could result in savings hundreds of millions in health care spending each year in the US alone.4,6 However, a recent argument has been made that the cost savings are not as high as might appear, mostly because a high percentage of subjects were switched to aflibercept early.5 A cost analysis study showed that, despite the large cost difference in the medications (aflibercept is 26 times more expensive than bevacizumab), with the bevacizumab-first approach, the overall costs were only 33% lower than aflibercept monotherapy at two years.